Respuesta :
Answer:
[tex]a+b+c+d = -5\cdot b[/tex]
Step-by-step explanation:
The given system of equations is now reduced:
1) [tex]a+b = c[/tex], [tex]b+c = d[/tex], [tex]c+d=a[/tex], [tex]b > 0[/tex] Given
2) [tex]a = c+d[/tex] By 1)
3) [tex](c+d)+b=c[/tex] 2) in 1)
4) [tex]d = b + c[/tex] By 1)
5) [tex][c+(b+c)]+b = c[/tex] 4) in 3)
6) [tex]2\cdot b + 2\cdot c = c[/tex] Algebra
7) [tex]c = -2\cdot b[/tex] Algebra
8) [tex]d = -b[/tex] 7) in 4)/Algebra
9) [tex]a = -3\cdot b[/tex] 7) and 8) in 2)/Algebra
10) [tex]a+b+c+d = -5\cdot b[/tex] 9), 1), 7) and 8)/Algebra/Result